Gold(III)-catalyzed site-selective and divergent synthesis of 2-Aminopyrroles and Quinoline-based Polyazaheterocycles - Zeng, Zhongyi; Jin, Hongming; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Angewandte Chemie, 2018)
A facile, site-selective, and divergent approach to construct 2-aminopyrroles and quinoline-fused polyazaheterocycles enabled by a simple gold(III) catalyst from ynamides and anthranils under mild reaction conditions is described. This one-pot strategy uses readily available starting materials, proceeds in a highly step- and atom-economical manner, with broad substrate scope and scale-up potential. The key element for success in this tandem reaction is a catalyst-directed preferred quenching of the in situ generated gold carbene intermediates by a nucleophilic benzyl/2-furylmethyl moiety on the ynamides as an alternative to the known C−H annulation leading to indoles.